Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters. Issue 6 (15th August 2018) - Jabado, Rima W.; Kyne, Peter M.; Pollom, Riley A.; Ebert, David A.; Simpfendorfer, Colin A.; Ralph, Gina M.; Al Dhaheri, Shaikha S.; Akhilesh, K. V.; Ali, Khadeeja; Ali, Mohamud Hassan; Al Mamari, Tariq M. S.; Bineesh, K. K.; et al.
Abstract: The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.